2009
DOI: 10.1128/jvi.02196-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Defective Oct-2 and OCA-B Expression in Immunoglobulin Production and Kaposi's Sarcoma-Associated Herpesvirus Lytic Reactivation in Primary Effusion Lymphoma

Abstract: Primary effusion lymphoma (PEL) is a distinct type of B-cell non-Hodgkin lymphoma characterized by the presence of Kaposi's sarcoma-associated herpesvirus (KSHV/human herpesvirus 8). Despite having a genotype and gene expression signature of highly differentiated B cells, PEL does not usually express surface or cytoplasmic immunoglobulin (Ig). We show the lack of Oct-2 and OCA-B transcription factors to be responsible, at least in part, for this defect in Ig production. Like Ig genes, ORF50, the key regulator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 75 publications
1
14
1
Order By: Relevance
“…Interestingly, since both EBV and KSHV establish viral latency in B cells, this leads to the question of whether Oct-2 has an effect similar to that of Oct-1 in regulating lytic viral reactivation. In the case of KSHV, a recent report showed that Oct-2 functions as a negative regulator of viral reactivation by competing with Oct-1 for viral promoter octamer binding sites and thereby helps to promote viral latency in B cells (20). We have likewise found that Oct-2 inhibits, rather than promotes, lytic EBV reactivation (A. R. Robinson, S. Kwek, and S. C. Kenney, unpublished data).…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, since both EBV and KSHV establish viral latency in B cells, this leads to the question of whether Oct-2 has an effect similar to that of Oct-1 in regulating lytic viral reactivation. In the case of KSHV, a recent report showed that Oct-2 functions as a negative regulator of viral reactivation by competing with Oct-1 for viral promoter octamer binding sites and thereby helps to promote viral latency in B cells (20). We have likewise found that Oct-2 inhibits, rather than promotes, lytic EBV reactivation (A. R. Robinson, S. Kwek, and S. C. Kenney, unpublished data).…”
Section: Discussionmentioning
confidence: 65%
“…Down-regulation of Oct2 and its coactivator Bob-1 has been linked to abnormal Ig expression in Hodgkin and Reed-Sternberg (HRS) cells in Hodgkin disease (166, 167) and in primary effusion lymphoma (PEL) (168). Oct2 and Bob-1 are useful markers for the differential diagnosis of classic Hodgkin lymphoma (169).…”
Section: Pathophysiological Roles Of Oct Proteinsmentioning
confidence: 99%
“…Oct2 competes with Oct1, which enhances ORF50 transactivation. Thus, down-regulation of Oct2 may promote viral reactivation of HHV-8 (168). …”
Section: Pathophysiological Roles Of Oct Proteinsmentioning
confidence: 99%
“…Several cellular factors, such as XBP-1, Ras, Ets-1, PARP-1, hKFC, CBP, the SWI/SNF chromatin remodeling complex, the TRAP/Mediator complex, RBP-J, human Notch intracellular domain, and HMGB1, have been shown to promote KSHV reactivation and/or lytic gene expression (11,31,32,44,71,72,75,76), suggesting a close link between many cellular processes and KSHV reactivation. Other cellular factors, such as Oct-2, KAP-1, and Hey1, were found to inhibit KSHV reactivation and/or lytic gene expression (12,19,25). However, the regulation of KSHV reactivation by cellular signals is still not fully understood.…”
mentioning
confidence: 99%